Development of Electronic Water Meter Based on Wireless Network and RF - Gorenekli, K.; Becerikli, Y. (Engineering, Technology & Applied Science Research, 2019)
The global need for water is increasing. Water must be used more economically in order to be sustainable. Water consumption per capita in Turkey is below the world regarding its geographical location. Manual reading water meters are inconvenient and time-consuming, they have low accuracy, they are very slow and resource wasting. Using wireless communication will mitigate these unwanted states. Consumers will be able to observe their water consumption in real time and be able to compare with the average water consumption in their district. With this system water pressure of whole pipes could be observed.